2005
DOI: 10.1007/s11010-005-5074-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel antioxidant agent caffeic acid phenethyl ester prevents long-term mobile phone exposure-induced renal impairment in rat

Abstract: Caffeic acid phenethyl ester (CAPE), a flavonoid like compound, is one of the major components of honeybee propolis. It has been used in folk medicine for many years in Middle East countries. It was found to be a potent free radical scavenger and antioxidant recently. The aim of this study was to examine long-term applied 900 MHz emitting mobile phone-induced oxidative stress that promotes production of reactive oxygen species (ROS) and, was to investigate the role of CAPE on kidney tissue against the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 45 publications
3
31
0
3
Order By: Relevance
“…Ozguner et al 22 demonstrated the occurrence of free radicals in relation to mobile phone usage and their negative effects on rat kidneys. In Ragy's study, 23 the effect of 900 MHz EMR produced by mobile phones on the brain, liver and kidney tissues of male albino rats was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozguner et al 22 demonstrated the occurrence of free radicals in relation to mobile phone usage and their negative effects on rat kidneys. In Ragy's study, 23 the effect of 900 MHz EMR produced by mobile phones on the brain, liver and kidney tissues of male albino rats was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were maintained on a 24-hour light-dark cycle regiment at a temperature of [21][22][23][24] C with 50-55% relative humidity. All animals had free access to food and water.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Mobile phones manufactured using the latest technology operate in a high frequency range (300-3000 MHz). This further heightens concerns regarding the effect of mobile phones on human health (1). Most Global System for Mobile Communications (GSM) operators in Europe, Asia, and Africa use a frequency of 900 MHz (2).…”
Section: Introductionmentioning
confidence: 99%
“…These indicate that RF-EMR may act as a stressor on kidney tissue as well due to its sensitive ultrastructure to oxidative stress. Ozguner et al (21) investigated the effect on kidney tissue of exposure to 900 MHz RF-EMR in 8-week-old rats and reported an increase in MDA levels. MDA levels increased significantly in kidney and bladder tissue of rats exposed to the effect of a 900 MHz RF-EMR in adolescence compared to the control group (21).…”
Section: Discussionmentioning
confidence: 99%